Analisis Pengaruh Variasi Sudu terhadap Kinerja Kincir Angin Poros Horizontal - Noor, Muhammad Fathuddin; Dewi, Indah Noor Dwi Kusuma; Muhammad, Alief (TRANSMISI, 2022)
Indonesia is one of the countries with abundant natural resources that have the potential to become renewable energy at this time, the development of renewable energy is the focus of research because Indonesia is in the middle of the equator which makes more air movement, dependence on fossil fuels can be solved by using wind-powered energy. This study aimed to determine the performance of a horizontal axis windmill with a diameter of 30 cm with variations of 3 blades and 4 blades at a height of 22 meters from the ground. The results of the horizontal axis windmill research that has been carried out in this study can be seen that the wind speed at the 3 blade variation produces the lowest wind speed of 2.0 m/s with a blade rotation of 14.9 rpm and a generator output of 1.12 volts. The highest wind speed is 3.7 m/s with a blade rotation of 28.9 rpm and a generator output of 3.84 volts, while in variation 4 the lowest wind speed is 2.8 m/s with a blade rotation of 29.2 rpm and the generator output is 2.5 volts, while the highest wind speed is 4.3 m/s with a blade rotation of 42.2 rpm and the generator output is 4.9 volts.